Combining dynamin 2 myopathy and neuropathy mutations rescues both phenotypes - Marie Goret; Evelina Edelweiss; Jérémy Jehl; David Reiss; Patricio Aguirre-Pineda; Sylvie Friant; Jocelyn Laporte (Nature Communications)
Abstract Mutations within a single gene can lead to diverse human genetic diseases affecting highly specialized tissues. Notably, dominant mutations in the DNM2 gene, encoding the mechanoenzyme dynamin, lead to distinct neuromuscular disorders: centronuclear myopathy (CNM) and Charcot-Marie-Tooth neuropathy (CMT). CNM is characterized by myofiber structural anomalies while CMT presents peripheral nerve defects, both culminating in muscle weakness and atrophy. Despite their shared genetic origin, the mechanisms driving these diseases remain elusive, and no cure is available. Here, we present in vitro assays underlining opposing effects of DNM2 mutations, gain-of-function in CNM and loss-of-function in CMT. In vivo, we explored the potential compensatory effects of CNM and CMT mutations by breeding Dnm2 S619L/+ CNM with Dnm2 K562E/+ CMT mouse models. Dnm2 S619L/K562E offspring exhibit strongly improved motor coordination and muscle strength and mass, compared to single-mutant littermates. Dnm2 S619L/K562E mice present normalized muscle structure and nerve fiber organization. This study reveals that two distinct disease-causing mutations within the DNM2 gene compensate each other in vivo, leading to corrections of most individual phenotypes. The inverse modulation of DNM2 activity emerges as a promising therapeutic strategy to address CNM and CMT diseases.